The Role of the Four-dimensional Product in Achieve Competitive Advantage - Mohammed Abdul Wahid Flayyih; Ashwaq T.Kadhim (Journal of Madenat Alelem University College, 2020)
The research idea is based on developing the printed product in a self-time manner and the emergence of four-dimensional printing using the use of reactive polymeric raw materials in manufacturing. It helped to change the product itself when needed automatically. Modern manufacturing techniques are distinguished from traditional ones by adopting engineering, design and computer-aided manufacturing systems through advanced software packages in the field of engineering. As it is considered a key component of the manufacturing add-on system as a whole through design, analysis, manufacturing, operations and reduces the production cycle with the ability to add any design modifications and improve performance with the help of (3D CAD) by creating a database on which the process of engineering is based Inversely, unlike manufacturing in traditional industries, production is from the first step. Upon the final inspection of the product, if it does not conform to the specifications, all the previous operations were mainly wrong and ineffective and a burden on the company as it takes advantage of its best efforts to achieve the advantages above, but it wastes resources and is considered environmentally friendly in the case of cutting industry. Similar with little waste and lighter and stronger than traditional methods of production compared to manufacturing techniques in addition to the entire computer-managed to achieve time saving, costs and high quality, the research concluded that the development of the two-dimensional printer helped in the physical development of the printer Industrial by adding the third dimension (height) and adding the fourth dimension of time to be able to make a product.